The Impact of Industrial IoT (IIoT) and Edge Computing Adoption on the Operational Performance of Manufacturing Companies in Central Java - Susatyo Handoko; Karnoto Karnoto (West Science Interdisciplinary Studies, 2025)
This study investigates the impact of Industrial Internet of Things (IIoT) and Edge Computing implementation on the operational performance of manufacturing companies in Central Java. A quantitative research approach was employed, involving 150 respondents selected using purposive sampling. Data were collected through a structured Likert-scale questionnaire and analyzed using SPSS version 25, including descriptive statistics, correlation, and multiple linear regression. The results indicate that both IIoT and Edge Computing have a significant positive effect on operational performance, explaining 54% of the variance. Specifically, IIoT enhances real-time monitoring, predictive maintenance, and overall production efficiency, while Edge Computing reduces latency and accelerates data-driven decision-making. The findings provide practical insights for manufacturing managers seeking to optimize operations through advanced digital technologies.